PEMBERDAYAAN MASYARAKAT BERPARADIGMA ”PEOPLE CENTERED DEVELOPMENT” (PENANGGULANGAN DAMPAK BURUK PERTAMBANGAN DENGAN PEMETAAN DAN PEMANFAATAN MODAL SOSIAL) - Fitri Ramdhani Harahap; Sujadmi Sujadmi (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
Community empowerment in Gunung Muda Village, Riding Panjang, and Lumut Village, Belinyu Sub-district, Bangka Regency, Bangka Belitung Islands Province through the Community Empowerment Learning Program (KKN-PPM) aims to map and identify the fundamental problems experienced by the people of Bangka Belitung, especially the people in Gunung Muda Village, Riding Panjang, and Lumut Village, Belinyu Sub-district related to tin mining activities, plan and develop the potential of social capital owned by the community for the benefit of science and community welfare in Belinyu Sub-district and map potential social capital to be used as capital to overcome the adverse effects of tin mining. Empowerment activities with the People Centered Development approach as a people-centered participatory development model using social mapping and physical mapping methods. Social mapping and physical mapping focus on mapping the problems caused as a bad impact of tin mining faced by the community in Belinyu Sub-district. In an effort to map the social problems of the physical environment, what is done is to identify potential social capital and adverse effects of tin mining, find alternative solutions to handling adverse effects of tin mining, increase public awareness and knowledge related to handling adverse effects of tin mining, increase community and government participation, and form and strengthen the social institutional system in handling adverse effects of tin mining.The results of the implementation of activities as a form of KKN-PPM 2015 program found several methods outlined in the activities, namely (1) social mapping and physical mapping in an effort to identify potential social capital and adverse impacts of mining, (2) focus group discussions and socialization to find alternative solutions to handling adverse impacts of tin mining, (3) counseling and training to increase community awareness and knowledge, (4) counseling, training and site visits to increase community and government participation, and (5) group mentoring to form and strengthen the social institutional system in handling adverse impacts of tin mining.